HUBUNGAN PENGALAMAN LAPANGAN INDUSTRI DAN MOTIVASI KERJA DENGAN KESIAPAN KERJA LULUSAN PROGRAM STUDI PENDIDIKAN KESEJAHTERAAN KELUARGA - Rusmiati, Tika; Yulastri, Asmar,; Gusnita, Wiwik (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
The purpose of this study was to (1) analyze the relationship industry field experiencewith the job readiness of graduates, (2) analyze the relationship between workmotivation and job readiness of graduates, (3) analyze the relationship betweenindustry field experience and motivation to work with the job readiness of graduates.This research is a quantitative research using correlation approach. The datacollection technique using a questionnaire prepared by the